Perancangan Produk Makanan dan Kerajinan Dalam Meningkatkan Penjualan Pada Aplikasi Openchart Di Kec.Sungai Geringging - Yulinda, Monika; Zulfikar, Zulfikar; Rasolia, Riska (JOVISHE : Journal of Visionary Sharia Economy, 2024)
This research aims to design a sales system for food and craft products using a practical OpenChart CMS. Current technological developments have brought big changes to business people through digitalization, which provides opportunities for people who have businesses to further develop their businesses. to a wider network and increase the effectiveness of marketing their products. Solutions that can be utilized by business people include the use of E-Commers Platforms such as Openchart which offers various features to make product promotion easier. Openchart provides features that can helping MSMEs to market their products more effectively, in its use it requires a design and innovation strategy for the products to be sold that are no less attractive than foreign products. In Sungai Geringging District, MSMEs have great potential in the specialty food and craft business, but product marketing is still limited, namely traditional sales and is not widely known by the public, one of the factors inhibiting sales growth. Even though current technological developments and advances have encourage all food and craft products that are well known in the global market and are interested in various regions in Indonesia. This research uses a Research and Development (R&D) model with a 4D development model (Define, Design, Develop, Diissimenation). The Define at this stage is understanding the needs and problems that you want to solve. Design is the process of designing the initial concept of the product that will be developed. Develop (Development) is the stage of making, testing and improving products based on the design results. Diissimenation (deployment) is the final stage, namely introducing and distributing the product to a wider range of users. The results of this research are expected to provide practical solutions for MSMEs to make maximum use of digital technology in supporting their business growth.